Beyond energies: geometry predictions with the XYG3 type of doubly hybrid density functionals. Issue 96 (28th September 2016) - Su, Neil Qiang; Xu, Xin
Abstract : The scaled mean absolute deviations (s-MADs) of the optimized geometric parameters for covalent bondings (the CCse set), nonbonded interactions (the S22G30 set) and the transition state structures (the TSG36 set), with Tot referring to the averaged s-MAD for general performances. Abstract : The exchange–correlation functional holds the key to the success or failure of density functional theory calculations. When evaluating the functional performances, the current literature has focused much more on the ability of the method to reproduce exact electronic energies than on exact geometries. As all calculations have to start from the right geometries, the present feature article explores the functional performances on geometry predictions involving covalently and non-covalently bonded systems, as well as transition state structures with emphasis on the XYG3 type of doubly hybrid (xDH) functionals. The results are also presented for some challenging cases, demonstrating the usefulness of the xDH functionals in general.